Flying machine - Nahum, Andrew (New York: Alfred A Knopf, Inc., 1990)
A photo easy tracing the history and development of aircraft from hot-air balloons to jetliners. Includes information on the principles of flight and the inner workings of various flying machines
Includes index.
First published in 1990.
Keywords: Flying machine, Aeronautics -- Juvenile literature; Flying-machines -- Juvenile literature